Ethnocide and The Indigenous Aeta Magbukon - David, Neil Dimacali (Thai Journal of East Asian Studies, 2021)
This ethnographic study aimed to assess the facts and reasons for ethnocide on the part of the participants. It results from but is not limited to acculturation, assimilation, development, colonial mentality, and geography. The study found that while a significant number of participants have a good understanding of their material culture, their perception of how it is practiced is concerning. Their knowledge of their intangible culture is still sufficient for their continued creativity and existence, and such practice must be considered. Overall, the participants’ practice is torn between being kept and discarded. The participant’s perception of what causes ethnocide is dominated by a preference for a modern lifestyle, inability to speak the native dialect, non-speaking of the native dialect, and ethnic culture is not taught in-home or school. The majority of participants believe that their ethnic culture should be modified, preserved, or not practiced, particularly in terms of beliefs and practices. Most of the participants strongly agree on the importance of preserving ethnic culture for identity and solidarity.